Hyaluronic acid modified carbon nanotubes using for photothermal therapy by promoting apoptosis of nasopharyngeal carcinoma cells - Guo, Zeyu; Liu, Xianzhi; Lin, Yiyi; Sang, Zelin; Chen, Dong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The present work illustrates the role of multi-walled carbon nanotubes in photothermal therapy. Nasopharyngeal carcinoma (NPC) is a malignant tumor of the head and neck with significant ethnic and geographic differences, and conventional treatment options are no longer suitable to improve the prognosis and survival of patients. Photothermal therapy (PTT) has emerged as a new strategy for oncology treatment in recent years and is now used in the treatment of many common cancers. Multi-walled carbon nanotubes (MWCNT) have been used to advantage in several fields due to their excellent thermal conductivity. The aim of this paper is to investigate the promotion of apoptosis of nasopharyngeal cancer cells by multi-walled carbon nanotubes as an adjuvant nanomaterial for nasopharyngeal cancer photothermal therapy. Methods: Carboxylated multi-walled carbon nanotubes and prepared multiwalled carbon nanotube-hyaluronic acid (MWCNT-HA) composites were used for cell proliferation-related experiments such as CCK-8 assay, live-dead staining and flow cytometric analysis and inverted fluorescence microscopy to determine the expression level of apoptotic factors and confocal microscopy cell morphology analysis on nasopharyngeal carcinoma CNE-1 cells under near-infrared laser irradiation. The effects of multi-walled carbon nanotubes on the proliferation and apoptosis of tumor cells under NIR response were elucidated, and the mechanism of apoptosis was explored. Results: TEM and SEM demonstrated that MWCNT had good appearance morphology and the temperature rise curve indicated excellent photothermal stability. And MWCNT and MWCNT-HA could significantly inhibit the proliferation of tumor cells and change the normal morphology of cells under NIR laser irradiation. Cellular immunofluorescence analysis confirmed that MWCNT-HA significantly up-regulated the expression level of apoptosis factor Caspase-3 and significantly down-regulated the expression level of anti-apoptosis factor Bcl-2.In this study, MWCNT inhibited the proliferation of tumor cells and promoted apoptosis through the use of multi-walled carbon nanotubes as an adjuvant nanomaterial for photothermal therapy. In addition, multi-walled carbon nanotubes could inhibit the mitochondrial pathway of CNE-1 cells to cause cell death. These studies suggest that multi-walled carbon nanotubes can function as efficient photothermal conversion materials for tumor photothermal therapy.